SPIRITUALITAS SANTO IGNATIUS DE LOYOLA: DISKRESI ROH DAN RELEVANSINYA BAGI KEHIDUPAN IMAN KONTEMPORER - Maximilian Edward Tjang; Fanny Indarto; Yanto Sandy Tjang (STP St. Bonaventura Medan, 2026)
The study examines the spirituality of Saint Ignatius of Loyola by positioning the discernment of spirits as the core of the Ignatian faith experience and by exploring its relevance within the context of contemporary Christian life. Drawing on Saint Ignatius of Loyola’s conversion experience as processed through profound reflection, the study demonstrates that Ignatian spirituality developed as an approach to faith rooted in the dynamics of the human interior life and in openness to the action of the Holy Spirit within concrete life situations. Employing a qualitative method through library research, the study analyzes the principal works of Saint Ignatius of Loyola, particularly the Spiritual Exercises, as well as relevant contemporary literature in spiritual theology. The findings indicate that the discernment of spirits cannot be reduced to a form of psychological introspection; rather, it constitutes an integrative spiritual process that engages reason, affectivity, and the will in responsible decision-making oriented toward Gospel values. The Spiritual Exercises are understood as a holistic method of personal transformation, while the principles of finding God in all things and magis affirm the continuing relevance of Ignatian spirituality in addressing the challenges of the modern world. Accordingly, Ignatian spirituality offers a reflective, dialogical, and transformative framework of faith for contemporary Christian living.